Teaching and learning algebra in attractive ways: Perception and acceptance of pre-diploma students in UiTM Jengka, Pahang / Nik Muhammad Farhan Hakim Nik Badrul Alam, Fadila Amira Razali and YM Tengku Noorhalina YM Tengku Ahmad Putra - Nik Badrul Alam, Nik Muhammad Farhan Hakim; Razali, Fadila Amira; YM Tengku Ahmad Putra2, YM Tengku Noorhalina (Universiti Teknologi MARA Cawangan Pahang, 2021)
Algebra is one of the basic topics in Mathematics and it is quite abstract as it involves non-number or unknowns. This nature of algebra has caused difficulties among students worldwide in understanding the topic. Using attractive ways in understanding algebra helps teachers to provide better explanation such that students understand the topic in a better way. Since algebra is one of the main topics in Intensive Mathematics I (MAT037) which is a compulsory course for students taking pre-diploma in commerce in UiTM, it is very important to introduce the attractive and simpler methods in solving the mathematical problems. Some new and interesting methods are introduced to the students to see if their performance improves throughout the course. 57 of the students from UiTM Jengka, Pahang are given a survey to study their understanding and interest in learning mathematics before and after taking the course. The results show that using these attractive techniques in solving mathematical questions help them perform better in examinations. Their interest towards the subject has also improved. Hence, it is applicable to use these techniques in teaching future students.